Expression of interleukin-8 detected by in situ hybridization correlates with worse prognosis in primary cutaneous melanoma - Nürnberg, Wolf; Schadendorf, Dirk (The journal of pathology, 2000)
Previous in vitro studies have demonstrated that endogenously produced human interleukin-8 (IL-8) can act as an important growth factor for human melanoma cells in vitro. The present study, has investigated whether IL-8 mRNA expression in primary melanomas may be of prognostic relevance with regard to melanoma progression and metastatic spread. In order to evaluate the clinical significance of IL-8 mRNA expression of melanoma cells in vivo, 59 melanocytic tissue specimens (37 primary melanomas and 22 melanocytic naevi) were studied using a semiquantitative in situ hybridization technique. Significant mRNA expression of IL-8 was found in 59 per cent (22/37) of melanomas. In 19 per cent (7/37) of the malignant melanomas, additional hybridization signals were noted within keratinocytes of the overlying epidermis. In contrast, paralesional normal-appearing epidermis and melanocytes in non-malignant lesions (melanocytic naevi) showed no IL-8 mRNA. Analysis of the relationship between IL-8 expression and clinico-histopathological features showed a significant association between IL-8 mRNA expression and the histological melanoma subtype (IL-8 mRNA: 14/19 in superficial spreading melanoma versus 4/12 in nodular melanoma, p< 0·05). Furthermore, IL-8 expression in primary tumours could be correlated with the patients' clinical course, with time to progression being significantly reduced in primary tumours expressing IL-8 in either the tumour cells or keratinocytes of the overlying epidermis. These results demonstrate for the first time that IL-8 expression, as detected by in situ hybridization in primary tumours, may serve as a significant prognostic factor for tumour progression in human malignant melanoma.